Organophosphorus Compound as Suicidal Poison in Rural Areas of Bangladesh: A Medicolegal Study (Journal of Monno Medical College, 2023)
Background: Suicide by poisoning is a major public health problem in Bangladesh and other developing countries in the world. Among the poisonous substances, Organophosphorus compounds (OPC) poisoning is more common. Easy accessibility of the poison is the number one reason for the preference of OPCs as suicidal agents.Objective: This study was designed to find out demographic characteristics and postmortem findings related to suicide by OPC poisoning in Manikganj.Methodology: This retrospective cross-sectional study was carried out during January, 2019 to December, 2020 in the district hospital, Manikganj, Bangladesh.Results: During the study period, a total of 381 medico-legal autopsy have been done- among them, 83 (21.78%) cases were death due to OPC poisoning. Maximum (24, 28.91%) deaths were between ages of 21-30 years, among them majority were males (49, 59.03%). People of different occupations were involved in OPC poisoning- maximum of them were housewives (27, 32.53%), followed by agricultural workers (13, 15.66%). Regarding motive of poisoning, the most common was suicidal intent (58, 69.88%) among both males (22, 37.93%) and females (36, 62.07%), followed by accidental (25, 30.12%). About one third of the cases were illiterate (26, 31.33%). Financial constraint was the main cause of suicide. Conclusion: OPC poisoning is a burning problem in our health sector. Improvement of awareness, elimination of unemployment, financial stability, limiting availability and banning more toxic compounds would reduce the OPC poisoning rate to a considerable number.Journal of Monno Medical College, June 2023; 9 (1): 07-10